2019
DOI: 10.1158/1535-7163.mct-18-0448
|View full text |Cite|
|
Sign up to set email alerts
|

Oleanolic Acid Inhibits Epithelial–Mesenchymal Transition of Hepatocellular Carcinoma by Promoting iNOS Dimerization

Abstract: Oleanolic acid exhibits extensive pharmacologic activities and takes significant antitumor effects. Its pharmacologic mechanism, however, still remained to be further clarified. In this study, we demonstrated that oleanolic acid attenuated the migration and invasion abilities, resulting in the suppression of the epithelial-mesenchymal transition (EMT) process in liver cancer cells, and inhibited the tumor growth of the peritoneal lymphocytes-bearing mice. We further proved that inducible nitric oxide synthase … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 44 publications
1
44
0
Order By: Relevance
“…Given its anti-tumor effects displayed in liver cancer, oleanolic acid coupled to regorafenib has been tested for advanced HCC. Both agents acted synergistically to inhibit the proliferation, EMT, migration and invasion of the PLC/PRF/5 cell line, which agrees with the suppression of tumor growth and lung metastasis in PLC-bearing mice 37 . In the same way, chlorogenic acid, a polyphenol present in the human diet, has shown positive effects in vitro in conjunction with regorafenib.…”
Section: Regorafenib and Hccsupporting
confidence: 76%
“…Given its anti-tumor effects displayed in liver cancer, oleanolic acid coupled to regorafenib has been tested for advanced HCC. Both agents acted synergistically to inhibit the proliferation, EMT, migration and invasion of the PLC/PRF/5 cell line, which agrees with the suppression of tumor growth and lung metastasis in PLC-bearing mice 37 . In the same way, chlorogenic acid, a polyphenol present in the human diet, has shown positive effects in vitro in conjunction with regorafenib.…”
Section: Regorafenib and Hccsupporting
confidence: 76%
“…Various studies observed these transitions to prove that the tested natural product was able to regulate EMT. For example, a recent study performed by Wang et al showed that oleanolic acid from olives inhibits the expression of mesenchymal-related protein (vimentin) while retaining the E-cadherin expression of hepatocellular carcinoma cell [57]. Other research on the action of Olea europaea and its active compounds on EMT pathway also reported the same pattern (Table 1); the affected pathway can be divided into two types: the SMAD-dependant and -independent pathways.…”
Section: Involvement Of Olea Europaea and Its Active Compounds In mentioning
confidence: 81%
“…ex Miq. extraction) has antioxidant activity and attenuates tumor progression via inhibiting epithelial-mesenchymal transition (EMT) (Bai et al, 2018;Wang et al, 2018). Moreover, our previous study found that AAM could effectively prevent CRC progression via inhibiting tumor angiogenesis and vasculogenic mimicry (VM) in murine model (Manman Yu et al, 2011;Hou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%